Schaum's outlines of programming with c++ Programming with C++ - Hubbard, J. R. (John Rast), 1943-; Baxter, Anthony Q.; Hubbard, J. R. (John Rast), 1943- (New York : McGraw-Hill, 2000)
A crash course that includes fully solved problems for every topic, expert tips for mastering Programming with C++, and all you need to know to pass the course.
"Based on Schaum's outline of programming with C++.".
Includes index.
All age.
Keywords: C++ (Computer program language).